Evaluation of hepatotoxicity potential of a potent traditional Tibetan medicine Zuotai. (24th April 2019) - Zhou, Liang-Liang; Chen, Hai-Juan; He, Qiang-Qiang; Li, Cen; Wei, Li-Xin; Shang, Jing
Abstract: Ethnopharmacological relevance: Zuotai (gTso thal) has a long history in the treatment of cardiovascular disease, liver and bile diseases, spleen and stomach diseases as a precious adjuvant in Tibetan medicine. However, Zuotai is a mercury preparation that contains 54.5% HgS. Its application has always been controversial. Aim of the study: To evaluate the toxicological effects of Zuotai in hepatocytes and in zebrafish. Materials and methods: MTT was used to determine the survival rate of hepatocytes; Hoechst and TUNEL staining were used to detect the apoptosis cells; Western blot and RT-qPCR assay were used to determine the expression levels of the protein and mRNA; Liver morphology observation and H&E staining were used to evaluate the hepatotoxicity of Zuotai in Zebfrafish. Results: The survival rate of L-02 cells, HepG2 cells and RBL-2A cells reduced by Zuotai (10 −4 –0.1 mg/mL) in a dose and time-dependent manner. Zuotai (0.1 mg/mL) induced HepG2 cells shrinkage, condensation and fragmentation and increased the number of apoptosis cells. The protein expression levels of cleaved Caspase-3 and Bax were increased and the expression levels of Bcl-2 were reduced after HepG2 cells exposed to Zuotai (10 −4 –0.1 mg/mL) for 24 h. In addition, Zuotai (0.2 mg/mL) induced the darker liver color of the larval zebrafish and changed the liver morphologic of adult zebrafish. Zuotai (0.2 mg/mL) also increased the mRNA levels of CYP1A1, CYP1B1 and MT-1 in the liver of adult zebrafish. However, no significantly hepatotoxicity was observed after hepatocytes and zebrafish exposed to HgS at the same dose. Conclusions: Results showed that Zuotai induced hepatotoxicity effectively under a certain dose but its hepatotoxicity likely occurs via other mechanisms that did not depend on HgS. Graphical abstract: Zuotai, a clinical adjuvant in Tibetan medicine, contains 54.5% HgS, which can induce apoptosis of liver cells and liver injury in zebrafish. However, HgS, the principal component of Zuotai did not exhibit hepatotoxicity at the same dose.fx1